Implementation of Merdeka Learning Curriculum with Pancasila Student Profile Strengthening Project at State Primary School - Rahman, Gusri Andi; Widayatsih, Tri; Nurlina, Nurlina (Journal of Social Work and Science Education, 2024)
This study aims to describe the implementation of the Merdeka learning curriculum and the Pancasila student profile strengthening project, as well as the obstacles and impacts that arise from its implementation. This study uses a descriptive qualitative research method. The informants taken in this study were 5 people who were directly related to this study. The data collection techniques obtained were observation, interviews, and documentation in data analysis using data reduction, data presentation, and conclusions. The results of this study indicate that the implementation of the Merdeka learning curriculum and the Pancasila student profile strengthening project have been implemented in stages at SD Negeri 03 Rantau Alai and are running well as intracurricular and co-curricular learning. Problems that arise in the implementation of the Merdeka learning curriculum and the Pancasila student profile strengthening project are the lack of relevant reading books, teacher competence in the use of supporting technology, and limited internet access. All existing obstacles have been overcome by adding relevant reading books, conducting teacher training forming learning communities, and adding signal boosters (modems).